Răspuns:
a) ( [tex]x^{2}[/tex] -9) ( [tex]x^{2}[/tex] +9) - ([tex]x^{4} +4x^{2} +4[/tex]) + 2([tex]x^{2} +4x+4)[/tex]=
[tex]x^{4}[/tex] -81 - [tex]x^{4}[/tex] -4 [tex]x^{2}[/tex] - 4 +2[tex]x^{2}[/tex]+8x +8= - 2[tex]x^{2}[/tex] +8x -77
b) ([tex]a^{2} - 4[/tex]) ([tex]a^{2}[/tex]+4) - [tex]a^{4}[/tex] - [tex]a^{2}[/tex] - 1 +2 ([tex]a^{2}[/tex] +2a +1)=
[tex]a^{4}[/tex] - 16 - [tex]a^{4}[/tex] - [tex]a^{2}[/tex] - 1 + 2[tex]a^{2}[/tex] + 4a +2= [tex]a^{2}[/tex] +4a - 15
c) ( [tex]x^{2} -1[/tex]) ([tex]x^{2}[/tex]+1) - [tex]x^{4}[/tex] - 6[tex]x^{2}[/tex] - 9+ 6[tex]x^{2}[/tex] -12x -24=
[tex]x^{4}[/tex] -1 - [tex]x^{4}[/tex] - 9 -12x-24= -12 x- 34